Genomic repertoires linked with pathogenic potency of arthritogenic Prevotella copri isolated from the gut of patients with rheumatoid arthritis. Issue 5 (10th January 2023) - Nii, Takuro; Maeda, Yuichi; Motooka, Daisuke; Naito, Mariko; Matsumoto, Yuki; Ogawa, Takao; Oguro-Igashira, Eri; Kishikawa, Toshihiro; Yamashita, Makoto; Koizumi, Satoshi; Kurakawa, Takashi; Okumura, Ryu; et al.
Abstract : Objectives: Prevotella copri is considered to be a contributing factor in rheumatoid arthritis (RA). However, in some non-Westernised countries, healthy individuals also harbour an abundance of P. copri in the intestine. This study investigated the pathogenicity of RA patient-derived P. copri ( P. copri RA ) compared with healthy control-derived P. copri ( P. copri HC ). Methods: We obtained 13 P . copri strains from the faeces of patients with RA and healthy controls. Following whole genome sequencing, the sequences of P. copri RA and P. copri HC were compared. To analyse the arthritis-inducing ability of P. copri, we examined two arthritis models (1) a collagen-induced arthritis model harbouring P. copri under specific-pathogen-free conditions and (2) an SKG mouse arthritis model under P. copri -monocolonised conditions. Finally, to evaluate the ability of P. copri to activate innate immune cells, we performed in vitro stimulation of bone marrow-derived dendritic cells (BMDCs) by P. copri RA and P. copri HC . Results: Comparative genomic analysis revealed no apparent differences in the core gene contents between P. copri RA and P. copri HC, but pangenome analysis revealed the high genome plasticity of P. copri . We identified a P. copri RA -specific genomic region as a conjugative transposon. In both arthritis models, P. copri RA -induced more severe arthritis than P. copri HC . In vitro BMDC stimulation experiments revealed the upregulation of IL-17 and Th17-related cytokines (IL-6, IL-23) by P. copri RA . Conclusion: Our findings reveal the genetic diversity of P. copri, and the genomic signatures associated with strong arthritis-inducing ability of P. copri RA . Our study contributes towards elucidation of the complex pathogenesis of RA.